Hired Latinx child farm labor in North Carolina: The demand‐support‐control model applied to a vulnerable worker population. Issue 12 (22nd August 2019) - Quandt, Sara A.; Arnold, Taylor J.; Mora, Dana C.; Sandberg, Joanne C.; Daniel, Stephanie S.; Arcury, Thomas A.
Abstract: Background: US government child labor policies allow children as young as age 10 to be hired as workers on farms not operated by family members. Children may face substantial health risks in an industry known for high worker morbidity and mortality rates, due to high demands for productivity, and low control and little support because of the organization of the workplace. This paper examines how child farmworkers in North Carolina experience their work situation. Methods: In‐depth interviews conducted in 2016 with 30 Latinx child farmworkers, ages 10 to 17, were analyzed using concepts from the demand‐control‐support model. All had worked as either migrant or seasonal hired farmworkers within the past year. Results: Children reported planting, cultivating, and harvesting crops including fruits, vegetables, and tobacco. The crew leader supervisory system, piece‐rate pay, and coworker pressure produced significant demands to work quickly and take risks including lifting heavy loads, operating mechanical equipment, and working in excessive heat. Children had little control over work to counter demands they experienced; and they labored in a state of fear of firing, wage theft, and other sanctions. Support was variable, with younger children more likely to experience family and coworker support than older children. Conclusions: The high demands with limited control and, for some, little support, that these children experience place them at risk and show the possibility of injury and exploitation. Future research should systematically document the occupational injury and illness of hired child farmworkers, and consider whether changes in labor policy are warranted.